Quantitative ethnobotanical appraisal of Shawal Valley, South Waziristan, Khyber Pakhtunkhwa, Pakistan - Ullah, Hekmat; Qureshi, Rahmatullah; Munazir, Mehmooda; Bibi, Yamin; Saboor, Abdul; Imran, Muhammad; Maqsood, Muhammad (Ethnobotany Research and Applications, 2023)
Background: This study’s primary goal was to collect and document uses of plants by local residents of Shawal Valley, South Waziristan, Pakistan. Methodology: A semi-structured questionnaire was used to interview 65 residents (24 women and 41 males). The Relative Frequency of Citation (RFC), Use Value (UV), Fidelity Level (FL), Informant Consensus Factor (ICF), and Jaccard Index (JI). Results: The research region is abode of 60 plant species belonged to 32 families of ethnobotanical significance. Lamiaceae family contributed maximum number of species (7), followed by Pinaceae (6 species). The most preferred plant parts among the reported species were the leaves (60%), followed by the stem (28.3%). Thymus mongolicus was found to have the highest RFC (0.86), while Adiantum capillus-veneris had the lowest (i.e. 0.02). The UV was between 0.02 and 1. Thymus mongolicus was found to have the greatest UV (UV=1); whereas, Adiantum capillus-veneris had the lowest UV (0.02). Twelve plants had a fidelity level of 100% while Quercus dilatata had the lowest (33.3%). Plants’ ICF values varied from 0.87 to 0.96. The Average Direct Matrix Ranking revealed that Quercus dilatata received the highest rating (1st) for its many uses, followed by Pinuswallichiana (2nd), and Rumex dentatus (3rd), Pinus gerardiana (4th), and Zingiberofficinale (5th). Conclusion:Ethnomedicinal research indicates that indigenous people in the studied area are knowledgeable on the use of plants. These plants and indigenous knowledge must be preserved.